Penggunaan Kontaktor pada Sistem Pengaman Motor Induksi 3 Phasa - Kalika Khaldan Nurshofa; Aldi Fadillah Ramadan; Nur Fajri Faiz; Paul Manurung; Diajeng Luluk Karlina (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
Three-phase induction motors are electric motors that are widely used in the industry due to their reliability and efficiency. However, these motors are prone to disturbances such as unstable voltages, overloads, and short circuits, which can cause serious damage. To protect the motor, a reliable safety system is required. This article discusses the role of magnetic contactors in the safety system of three-phase induction motors, including their working principles, types of contactors, and their application to protect motors from electrical interference. The contactor functions as an electromagnetic switch that can connect and disconnect electricity automatically, improving operator safety by enabling remote operation. In addition, this safety system is equipped with sensors that monitor electrical parameters, allowing for a quick response to disturbances. Thus, the use of contactors in the safety system of three-phase induction motors is essential to maintain reliability and safety.